2015
DOI: 10.1242/dev.117572
|View full text |Cite
|
Sign up to set email alerts
|

α5 and αv integrins cooperate to regulate vascular smooth muscle and neural crest functions in vivo

Abstract: The RGD-binding α5 and αv integrins have been shown to be key regulators of vascular smooth muscle cell (vSMC) function in vitro. However, their role on vSMCs during vascular development in vivo remains unclear. To address this issue, we have generated mice that lack α5, αv or both α5 and αv integrins on their vSMCs, using the SM22α-Cre transgenic mouse line. To our surprise, neither α5 nor αv mutants displayed any obvious vascular defects during embryonic development. By contrast, mice lacking both α5 and αv … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 89 publications
3
31
0
Order By: Relevance
“…Similarly, Turlo et al (2012) used the SM22α-Cre transgenic line to ablate integrin β1 and showed that the expression of β1-containing integrin heterodimers, which include α5β1, in smooth muscle cells was important for maintaining AAA VSMCs and AAA integrity. Taken together with the studies by Turlo et al (2012) and Turner et al (2015), our work demonstrates that signaling by Fn1 and integrin α5β1 is essential for both the morphogenesis and maintenance of the AAAs: our studies establish the requisite role of Fn1 and integrin α5β1 in the differentiation of NC cells into VSMCs, thereby regulating the remodeling of symmetrical PAAs into the AAAs. The work of Turlo et al (2012) and Turner et al (2015) demonstrated that following the differentiation of NC cells into VSMCs, signaling by α5-, αv-and β1-containing integrin heterodimers is essential for maintaining VSMCs and the architecture of the AAA vessel wall.…”
Section: Early and Late Roles Of Fn1-binding Integrins In Aaa Morphogsupporting
confidence: 74%
See 3 more Smart Citations
“…Similarly, Turlo et al (2012) used the SM22α-Cre transgenic line to ablate integrin β1 and showed that the expression of β1-containing integrin heterodimers, which include α5β1, in smooth muscle cells was important for maintaining AAA VSMCs and AAA integrity. Taken together with the studies by Turlo et al (2012) and Turner et al (2015), our work demonstrates that signaling by Fn1 and integrin α5β1 is essential for both the morphogenesis and maintenance of the AAAs: our studies establish the requisite role of Fn1 and integrin α5β1 in the differentiation of NC cells into VSMCs, thereby regulating the remodeling of symmetrical PAAs into the AAAs. The work of Turlo et al (2012) and Turner et al (2015) demonstrated that following the differentiation of NC cells into VSMCs, signaling by α5-, αv-and β1-containing integrin heterodimers is essential for maintaining VSMCs and the architecture of the AAA vessel wall.…”
Section: Early and Late Roles Of Fn1-binding Integrins In Aaa Morphogsupporting
confidence: 74%
“…Known embryonic sources of VSMCs include the lateral and paraxial mesoderm, mesothelia and the NC (Jiang et al, 2000;Le Lievre and Le Douarin, 1975;Que et al, 2008;Rinkevich et al, 2012;Wasteson et al, 2008;Wilm et al, 2005). Studies by others and our lab indicated that integrin α5 is not required for the differentiation of mesodermal cells into VSMCs Turner et al, 2014Turner et al, , 2015. Furthermore, addition of Fn1 to mesodermal VSMC precursors stimulated their proliferation and the synthetic phenotype and opposed their differentiation into smooth muscle cells (Bae et al, 2014;Hedin et al, 1988;Shi et al, 2014).…”
Section: Early and Late Roles Of Fn1-binding Integrins In Aaa Morphogmentioning
confidence: 75%
See 2 more Smart Citations
“…Typically, VSMC-specific knockout of integrin receptor subunits such as b1 [156], a4 [157], a7 [158], a5, and av [159], but not a5 alone [160], yields similar phenotypes with disturbed mural recruitment and vessel organization. However, these defects are not the result of ablated mural differentiation, but rather impaired migration, proliferation, and association with maturing vessels.…”
Section: Biochemical Signaling In the Ecmmentioning
confidence: 99%